Changes in energy and nutrient intakes among Malaysian adults: findings from the Malaysian Adult Nutrition Survey (MANS) 2003 and 2014 - Zainuddin, Ahmad Ali; Md Nor, Norazmir; Md Yusof, Safiah; Ibrahim, Adriana Irawati Nur; Aris, Tahir; Foo, Leng Huat (Nutrition Society of Malaysia, 2019)
Introduction: Monitoring changes in energy and nutrient intakes of the population over the course of time is essential to help healthcare providers develop effective dietary policies. The aim of this study was to assess the changes in the nutrient intake and Recommended Nutrient Intake (RNI) achievements by using the data obtained from the Malaysian Adult Nutrition Surveys (MANS) that were carried out in 2003 and 2014. Mis-reporting of energy intake was taken into account. Methods: Dietary data were obtained from MANS 2003 and MANS 2014, which involved a combined total of 4,044 randomly selected respondents, aged 18-59 years, using a single 24-hour diet recall. Energy and nutrients calculations were based on the Malaysian Food Composition database using the Nutritionist Pro software. The results were compared against the RNI for Malaysia to assess dietary adequacy. Results: The proportions of calories derived from macronutrients were within the recommendations for a healthy diet. The consumption of protein, fat, calcium, iron and vitamin A was significantly higher in 2014 than in 2003. The consumption of protein, iron, vitamin C, and vitamin A was found to exceed the RNIs in 2014. However, carbohydrate and sodium intakes had significantly decreased. Despite the decrease, sodium intake still exceeded RNI recommendations. Conclusion: Signs of changing energy and nutrient intakes were found, including increases in protein and fat intakes since 2003, and decreased carbohydrates. This could be an alarming indicator of the tendency to eat energy dense food among the population. © 2019, Malaysian Journal of Nutrition.